Skilled interpersonal communication : research, theory and practice - Hargie, Owen, ....- (Oxon : Routledge, 2017)
There is a fundamental, powerful, and universal desire amongst humans to interact with others. People have a deep-seated need to communicate, and the greater their ability in this regard the more satisfying and rewarding their lives will be. The contribution of skilled interpersonal communication to success in both personal and professional contexts is now widely recognised and extensively researched. As such, knowledge of various types of skills, and of their effects in social interaction, is crucial for effective interpersonal functioning. Previous editions have established Skilled Interpersonal Communication as the foremost textbook on communication. This thoroughly revised and expanded 6th edition builds on this success to provide a comprehensive and up-to-date review of the current research, theory and practice in this popular field of study. The first two chapters introduce the reader to the nature of skilled interpersonal communication and review the main theoretical perspectives. Subsequent chapters provide detailed accounts of the fourteen main skill areas, namely: nonverbal communication; reinforcement; questioning; reflecting; listening; explaining; self-disclosure; set induction; closure; assertiveness; influencing; negotiating; and interacting in, and leading, group discussions. Written by one of the foremost international experts in the field and founded solidly in research, this book provides a key reference for the study of interpersonal communication. This theoretically informed, yet practically oriented text, will be of interest both to students of interpersonal communication in general, and to qualified personnel and trainees in many fields.
Keywords: Interpersonal communication